Estimulación temprana y el desarrollo cognitivo de niños y niñas de 0 a 2 años de edad del centro infantil el buen vivir C.I.B.V. - Mora Angulo, Carolina Stefanía (2016)
The present time require the presence of educational institutions to lay down models methods, techniques and traditional teaching strategies and give way to educational innovation in the context of which form school with levels of critical and creative thinking reproductivetransference. The use of educational resources lacking meaning the lack of classroom and intellective corners in early childhood education are problems that prevent toddlers master skills related tocognitive development….